Preparation And Ultrasonic Characterization Of Fresh Concrete - Mohamed@Ahmad, Mohd Noorul Ikhsan (2009)

(untitled)
An ultrasonic based device has been developed to estimate the age of fresh concrete. The concrete that used in this study is grade 30 concrete. The mix design of concrete samples is calculated using software called Calcrete. All concrete samples used throughout the study was Grade 30 concrete with water to cement ratio (w/c) 0.5 apart for the effect of casting time on concrete strength test, there were two different mixtures used. Mixture 1 (Mix 1) is concrete grade 30 with the w/c ratio of 0.5 and for the Mixtures 2 (Mix 2), the w/c ratio is 0.65. The slump value of each mixed concrete was successfully measured. There were three types of moulds prepared for ultrasonic fresh concrete testing namely Mould 1, Mould 2 and Mould 3. Pre-testing of each fabricated moulds was conducted in order to select the appropriate mould for fresh concrete testing. The velocity of each fresh concrete was monitored within 4 hours using Mould 3. The preparation of same grade of concrete was repeated using the same method and left for 1 to 4 hour before the slump value was measured. The concrete samples cured in room temperature for 28 days. After 28 days, all concrete samples were tested for an ultrasonic property such as ultrasonic pulse velocity, acoustic impedance and acoustic modulus. The compression test was performed to obtain the strength properties of each sample. The experimental result shows that the slump value and ultrasonic pulse velocity of concrete decreased with the increasing of casting time. The slump tests indicate that concrete at 4 and 5 hour of casting time have no workability. Ultrasonic pulse velocity obtained is in the range of 1900 to 2400 m/s. The density, acoustic impedance and acoustic modulus of concrete also vary with the casting time. The density of concrete samples is between 1800 to 2300 kg/ m3. The acoustic impedance of concrete samples that were produced throughout project is in the range of 7 to 9 MRayl while the acoustic modulus is in the range of 26 to 35 GPa depending on time of casting.